A new global ocean ensemble system at the Met Office: Assessing the impact of hybrid data assimilation and inflation settings. (25th May 2022) - Lea, Daniel J.; While, James; Martin, Matthew J.; Weaver, Anthony; Storto, Andrea; Chrust, Marcin
Abstract: We have developed a global ocean and sea‐ice ensemble forecasting system based on the operational forecasting ocean assimilation model (FOAM) system run at the Met Office. The ocean model Nucleus for European Modelling of the Ocean (NEMO) and the community ice code (CICE) sea‐ice model are run at 1/4 ∘ ^° resolution and the system assimilates data using a three‐dimensional variational assimilation (3DVar) version of NEMOVAR. This data assimilation (DA) system can perform hybrid ensemble/variational assimilation. A 36‐member ensemble of hybrid ensemble variational assimilation systems with perturbed observations (values and locations) has been set up, with each member forced at the surface by a separate member of the Met Office Global–Regional Ensemble Prediction System (MOGREPS‐G). The unperturbed member is forced by atmospheric fields from the Met Office operational numerical weather prediction (NWP) deterministic system. The system includes stochastic model perturbations and a relaxation to prior spread (RTPS) inflation scheme. A control run of the system using an ensemble of 3DVars is shown to be generally reliable for Sea‐Level Anomaly (SLA), temperature, and salinity (the ensemble spread being a good representation of the uncertainty in the ensemble mean), although the ensemble is underspread in eddying regions. The ensemble mean gives a 4% reduction in error in SLA compared with the deterministic 3DVar system currently used operationally. The system was tested with different weights for the ensemble component of the hybrid background‐error covariance matrix and different inflation factors. The best results, in terms of short‐range forecast error and ensemble reliability statistics, were obtained with hybrid three‐dimensional ensemble variational DA (3DEnVar). The RTPS inflation scheme is shown to be beneficial in producing an appropriate ensemble spread in response to hybrid DA. 3DEnVar with an ensemble hybrid weight of 0.8 leads to a reduction of 20% (5%) in the ensemble mean error for SLA (profile temperature and salinity) compared with an ensemble of standard 3DVars. Abstract : Ensemble departure (standard deviation of the difference between ensemble mean and observations before assimilation), ensemble spread (at observation locations) and the standard deviation of the innovations for the unperturbed member for Sea Level Anomaly (in m), Sea Surface Temperature (in ∘ ^° C), profile temperature (in ∘ ^° C) and profile salinity (PSS) as a function of hybrid weight β e 2 β_e^2 . The unfilled symbol is an experiment without ensemble inflation. These are global ocean statistics from October to December 2018.